Strategies for Optimizing Village Markets as Village Economic Growth Centers in Central Java - Dela Lusiana Kartini (Journal of Community Service and Rural Development, 2024)
This study aims to develop a concrete strategic plan to maximize the potential of local markets as a driving force for rural economic growth, through a series of programs and initiatives to be implemented by relevant local agencies. The concepts applied in this study include Descriptive Analysis, which involves the evaluation of qualitative data obtained from focus group discussions. In addition, there is Qualitative Analysis, which leads to the evaluation of statements or data without numerical forms. Meanwhile, Quantitative Analysis involves the evaluation of numerical data and the generation of quantitative reports with the support of statistical analysis. The purpose of this analysis is to evaluate trends and calculate percentages. In this study, it was found that there is a need to improve the village market through several steps. First, efforts are needed to improve the physical infrastructure of the village market as well as improve the existing facilities. In addition, there is a need to improve the quality of human resources managing village markets, improve market management, and better support for permanent traders and street vendors in village markets. Currently, the development of village markets in Central Java has not fully followed the sustainable market model and has not capitalized on the potential for cooperation with the private sector in financing village market development.